Relationship between serum CA125, prolactin and cortisol levels with disease stage and pain level in endometriosis patients - Fasha, Teuku A.; Rajuddin, Rajuddin; Dewi, Tgk. Puspa; Rusnaidi, Rusnaidi; Munizar, Munizar (Narra J, 2026)
Endometriosis affects approximately 10% of women of reproductive age and is characterized by the presence of endometrial tissue outside the uterine cavity. Diagnostic delays are common due to nonspecific symptoms and the absence of reliable biomarkers. Serum CA125, prolactin, and cortisol have been implicated in the pathophysiology of endometriosis through inflammatory, neuroendocrine, and stress-response mechanisms. However, their role as biomarkers in endometriosis remains poorly studied. This study aimed to investigate the relationships between serum CA125, prolactin, and cortisol levels with endometriosis staging and pain severity in endometriosis patients. A cross-sectional study was conducted at Dr. Zainoel Abidin General Hospital, Banda Aceh, Indonesia, involving women with laparoscopically confirmed endometriosis. Serum CA125, prolactin, and cortisol levels were measured using electrochemiluminescence immunoassay (ECLIA). Disease staging followed the American Society for Reproductive Medicine (ASRM) classification, and pain severity was assessed using the Numeric Rating Scale (NRS). Statistical analyses were performed using the Spearman correlation test. A total of 30 women with confirmed endometriosis were included in this study, with a mean age of 37.2 years. Endometriosis stages were distributed as stage II (20.0%), stage III (16.7%), and stage IV (63.3%), and the mean pain score was 5.60±1.48. Elevated serum biomarker levels were observed with CA125 of 72.65±55.39 U/mL, prolactin of 1456.77±1799.79 μIU/mL, and cortisol of 341.92±189.02 nmol/L. The serum CA125 level was positively correlated with endometriosis staging (r=0.580, p=0.001) but not with pain severity. Prolactin and cortisol had no significant correlations with disease stage or pain severity (all p>0.05). This study shows that serum CA125 levels are significantly correlated with endometriosis staging, supporting its potential as a biomarker of disease progression. Although prolactin and cortisol levels were elevated, their lack of association with clinical parameters suggests broader neuroendocrine dysregulation rather than direct markers of disease severity.